The role of @literarybase X account in fulfilling information literation needs - Amani, Nisrina; Hadiapurwa, Angga; Khaerunnisa Syafitri, Nanda; Nugraha, Hafsah (Record and Library Journal, 2023)
Background of the study: X is a social media used mainly by the public as a source of information and can fulfill its users' information needs, including the @literarybase account, which discusses literature and books. Through this, it is expected to increase information literacy skills through information search activities to meet the information needs of its users. Purpose: This study aims to determine the role of auto-base @literarybase in meeting the information literacy needs of its followers. Method: The method used is quantitative with survey techniques. Data was collected online through the distribution of Google form questionnaires to followers of the @literarybase account with a Likert scale as a measurement, and analysis was carried out descriptively. Findings: The @literarybase account has played a role in meeting the information needs and training the information literacy skills of its followers. In content gratification, the @literarybase account fulfills the needs of information sharing and information seeking. In the gratification process, the @literarybase account fulfills entertainment, pass time, escape, habit, and self-expression needs. In social gratification, the @literarybase account fulfills the information needs through social interaction. Finally, regarding technology gratification, the @literarybase account fulfills information needs in the form of relative advantage. Conclusion: The @literarybase account has played a role in meeting information needs and training information literacy skills for its account followers. However, several aspects still need to be fully met, such as the need for self-document in content gratification, the need for campaigns in process gratification, the need for status seeking in social gratification, and the need for social compliance in technology gratification.